Adverse reactions to piperacillin in adults with cystic fibrosis. Issue 3 (March 1985) - Stead, R J; Kennedy, H G; Hodson, M E; Batten, J C
Abstract : Nine adult patients with cystic fibrosis, nearly a quarter of the 38 patients with this disease who were treated with piperacillin (59 courses in all) during 1981-3 at the Brompton Hospital, developed a swinging pyrexia after a mean of 13.5 days' treatment with this antibiotic. The fever resolved shortly after the piperacillin treatment was stopped, as did the widespread rashes in the two patients who developed them. Three of four patients who had probable reactions to azlocillin may have been sensitised by piperacillin. As piperacillin does not appear to be any more effective than other antipseudomonal penicillins in cystic fibrosis, it is no longer used at the hospital for treating bronchopulmonary exacerbations in such patients.